Asian low‐androstenone haplotype on pig chromosome 6 does not unfavorably affect production and reproduction traits. (29th September 2014) - Hidalgo, A. M.; Bastiaansen, J. W. M.; Harlizius, B.; Knol, E. F.; Lopes, M. S.; de Koning, D. J.; Groenen, M. A. M.
Summary European pigs that carry Asian haplotypes of a 1.94‐Mbp region on pig chromosome 6 have lower levels of androstenone, one of the two main compounds causing boar taint. The objective of our study was to examine potential pleiotropic effects of the Asian low‐androstenone haplotypes. A single nucleotide polymorphism marker, rs81308021, distinguishes the Asian from European haplotypes and was used to investigate possible associations of androstenone with production and reproduction traits. Eight traits were available from three European commercial breeds. For the two sow lines studied, a favorable effect on number of teats was detected for the low‐androstenone haplotype. In one of these sow lines, a favorable effect on number of spermatozoa per ejaculation was detected for the low‐androstenone haplotype. No unfavorable pleiotropic effects were found, which suggests that selection for low‐androstenone haplotypes within the 1.94 Mbp would not unfavorably affect the other eight relevant traits.